Real time kinetics of insulin-like growth factor II (IGF-II) interaction with the IGF-II/mannose 6-phosphate receptor: the effects of domain 13 and pH. - Linnell, J; Groeger, G; Hassan, A (2001)
The interaction of soluble forms of the human cation-independent insulin-like growth factor-II/mannose 6-phosphate receptor (IGF-IIR) with IGFs and mannosylated ligands was analyzed in real time. IGF-IIR proteins containing domains 1-15, 10-13, 11-13, or 11-12 were combined with rat CD4 domains 3 and 4. Following transient expression in 293T cells, secreted protein was immobilized onto biosensor chips. beta-Glucuronidase and latent transforming growth factor-beta1 bound only to domains 1-15. IGF-II bound to all constructs except a control, which contained a point mutation in domain 11. The affinity of domains 1-15, 10-13, 11-13, and 11-12 to IGF-II were 14, 120, 100, and 450 nm, respectively. Our data suggest that domain 13 acts as an enhancer of IGF-II affinity by slowing the rate of dissociation, but additional enhancement by domains other than 10-13 also occurs. As the receptor functions to transport ligands from either the trans-Golgi network or extracellular space to the endosomes, the interaction of IGF-IIR extracellular domains with IGF-II was analyzed over a pH range of 5.0-7.4. The constructs behaved differently in response to pH and in recovery after low pH exposure, suggesting that pH stability of the extracellular domains depends on domains other than 10-13.